Vortex arrays directly generated from an efficient diode-pumped microchip laser. (27th May 2020) - Chen, Dimeng; Miao, Yujie; Wang, Hanjie; Dong, Jun
Abstract: Optical vortex arrays with multiple singularities arranged in distinct lattice structures provide more flexibility in trapping or manipulating microparticles, large-capacity optical communications and high-security information processing, and optical modulation. An efficient high-power compact laser with singularity-tunable vortex-array distribution is crucial for practical applications. Here, we directly generate various vortex arrays with tunable singularities from 1 to 10 in a microchip laser pumped with a tilted annular beam. Formation of vortex arrays in the microchip laser is achieved by manipulating the gain distribution in an Yb:YAG crystal by controlling the tilt angles and pump power. Efficient high-power laser operation with output power of 2.01 W and optical efficiency of 24.5% is obtained for a vortex array with 10 singularities. The pump-power-dependent saturated population inversion distribution plays a key role in generating vortex arrays formed with multi-transverse modes oscillating simultaneously in transverse-mode locking. The good agreement between theoretically simulated transverse patterns, phases and interference patterns for the vortex arrays and experimentally obtained results provides a solid foundation for developing efficient compact microchip lasers for generating vortex arrays by manipulating gain distribution in a thin medium pumped with a tilted annular beam.